Answered

Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Solve, using the substitution method.

m + n = 5
m – n = 3


Sagot :

m + n = 5
m= n + 3

plug m=n+3 into the first equation. 

(n+3)+n=5
n+n+3=5
2n+3=5
2n=2
n=1

iGreen
First rearrange the first equation and solve it for 'm':

m + n = 5

Subtract n to both sides:

m = -n + 5

Now plug in -n + 5 for 'm' in the 2nd equation:

-n + 5 - n = 3

Combine like terms:

-2n + 5 = 3

Subtract 5 to both sides:

-2n = -2

Divide -2 to both sides:

n = 1

Now we can plug this back into any of the two equations and solve for 'm':

m + n = 5

m + 1 = 5

Subtract 1 to both sides:

m = 4

So our full answer is (4, 1)